Critical Discourse Analysis of Gender Equality and Feminism: A Comparative Study: Analisis Wacana Kritis tentang Kesetaraan Gender dan Feminisme: Studi - Silvia Alfi Rufaida; Sufyanto Sufyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This research compares gender equality and feminism in the 1931 Medan Sedar newspaper with Magdalene.co's article 'Wives of Sedar Towards Women's Work in Indonesia: Often Overlooked, Women's Careers Minimally Hopeful.' Grounded in a patriarchal culture fostering workforce gender disparities, Sara Mills' Critical Discourse Analysis is employed. Through documentary analysis and literature review, the findings show alignment between readers' perspectives and narrators. 'Wives of Sedar' reflects radical feminism, while 'Often Overlooked' portrays liberal feminism. In 1931, gender was a social construct rooted in patriarchy, contrasting with 2022's biological stereotype understanding. Presently, gender issues focus on task segregation. The feminist movement in Indonesia aligns with technological progress, advocating for gender equality. The research highlights evolving gender perceptions, offering insights for global scholars in understanding the historical and contemporary dynamics of gender and feminism. Highlights : The study delves into the historical context of gender representation in the 1931 Medan Sedar newspaper and compares it with contemporary perspectives in Magdalene.co's online magazine. Utilizing Sara Mills' Critical Discourse Analysis, the research unveils ideological shifts in feminist discourse, highlighting both radical and liberal feminist perspectives. The findings emphasize the evolution of gender concepts over time, from social constructs rooted in patriarchal culture to contemporary understandings shaped by technological advancements, offering valuable insights for global scholars. Keywords: Gender Equality, Feminism, Critical Discourse Analysis, 1931 Medan Sedar Newspaper, Magdalene.co Online Magazine